2022
DOI: 10.3389/fnmol.2022.1009662
|View full text |Cite
|
Sign up to set email alerts
|

Inferring miRNA sponge modules across major neuropsychiatric disorders

Abstract: The role of non-coding RNAs in neuropsychiatric disorders (NPDs) is an emerging field of study. The long non-coding RNAs (lncRNAs) are shown to sponge the microRNAs (miRNAs) from interacting with their target mRNAs. Investigating the sponge activity of lncRNAs in NPDs will provide further insights into biological mechanisms and help identify disease biomarkers. In this study, a large-scale inference of the lncRNA-related miRNA sponge network of pan-neuropsychiatric disorders, including autism spectrum disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Regarding PCA3 , it was extensively studied in cancer ( Lemos et al, 2019 ) and was found to be differentially expressed in the exosomes of cerebrospinal fluid of AD patients ( Gui et al, 2015 ). Finally, in a study focusing on the network of miRNA sponges for various neuropsychiatric disorders, including autism, HAR1A was identified as a candidate for this role in the autism spectrum disorder ( Balasubramanian and Vinod, 2022 ) and was also found to be downregulated in AD ( Li and De Muynck, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding PCA3 , it was extensively studied in cancer ( Lemos et al, 2019 ) and was found to be differentially expressed in the exosomes of cerebrospinal fluid of AD patients ( Gui et al, 2015 ). Finally, in a study focusing on the network of miRNA sponges for various neuropsychiatric disorders, including autism, HAR1A was identified as a candidate for this role in the autism spectrum disorder ( Balasubramanian and Vinod, 2022 ) and was also found to be downregulated in AD ( Li and De Muynck, 2021 ).…”
Section: Discussionmentioning
confidence: 99%